2017
DOI: 10.1002/path.5006
|View full text |Cite
|
Sign up to set email alerts
|

MYBL1 rearrangements and MYB amplification in breast adenoid cystic carcinomas lacking the MYBNFIB fusion gene

Abstract: Breast adenoid cystic carcinoma (AdCC), a rare type of triple-negative breast cancer, has been shown to be driven by MYB pathway activation, most often underpinned by the MYB-NFIB fusion gene. Alternative genetic mechanisms, such as MYBL1 rearrangements, have been reported in MYB-NFIB-negative salivary gland AdCCs. Here we report on the molecular characterization by massively parallel sequencing of four breast AdCCs lacking the MYB-NFIB fusion gene. In two cases, we identified MYBL1 rearrangements (MYBL1-ACTN1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 39 publications
(46 reference statements)
2
52
0
1
Order By: Relevance
“…Nuclear factors and their receptors are indispensable in the development of tumor growth, metastasis and epithelial-mesenchymal transition (EMT) in several types of cancers (8). Nuclear factor I/B (NFIB) is a recently discovered member of the nuclear factor family (which includes NFI-A, B and X) and emerging evidence has shown that NFIB, besides functioning during normal somatic development, is also involved in the generation and progression of various types of cancer, including small-cell lung cancer, melanoma and breast cancer, through different molecular mechanisms such as forming the oncogenic NFIB-MYB gene fusion or increasing the chromatin accessibilities of its downstream targets (9)(10)(11). Nevertheless, research on the functions and involvement of NFIB on the development of GC has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear factors and their receptors are indispensable in the development of tumor growth, metastasis and epithelial-mesenchymal transition (EMT) in several types of cancers (8). Nuclear factor I/B (NFIB) is a recently discovered member of the nuclear factor family (which includes NFI-A, B and X) and emerging evidence has shown that NFIB, besides functioning during normal somatic development, is also involved in the generation and progression of various types of cancer, including small-cell lung cancer, melanoma and breast cancer, through different molecular mechanisms such as forming the oncogenic NFIB-MYB gene fusion or increasing the chromatin accessibilities of its downstream targets (9)(10)(11). Nevertheless, research on the functions and involvement of NFIB on the development of GC has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in line with this study and support the use of MYB IHC as a useful adjunct to establishing the diagnosis of adenoid cystic carcinoma in the breast as well as non‐breast sites. Recent genetic investigations demonstrate that alternative mechanisms for MYB pathway activation including MYB amplification or rearrangement of MYBL1 (a closely related gene with similar function) may be present in a considerable number of ACC cases that lack the classic MYB–NFIB translocation . These provide a logical potential explanation for the observations that MYB expression by immunohistochemistry may be more sensitive for ACC of the breast compared to FISH.…”
Section: Discussionmentioning
confidence: 99%
“…Salivary gland ACC is driven by the MYB-NFIB gene fusion in the majority of cases, which has also been demonstrated in breast and lacrimal gland ACC, although much fewer cases have been examined (28,29,33,34,161,207). Recently, the identification of the MYBL1-NFIB gene fusion was shown to account for a subset of salivary gland and breast ACC without MYB-NFIB or the expression of MYB protein, whereas MYBL1 is yet to be shown to be involved in lacrimal gland ACC (21,30). We identified a spectrum of genetic abnormalities in salivary gland ACC, including MYB amplification (5 0 ), isolated MYB rearrangement (MYB-X), MYB-NFIB, MYBL1-NFIB, and isolated NFIB rearrangement (NFIB-X).…”
Section: Discussionmentioning
confidence: 99%